RISK MANAGEMENT IN CONSTRUCTION OF DRY BULK JETTY AT TELUK LAMONG MULTIPURPOSE TERMINAL - Bayu Puji Nugroho (NAROTAMA UNIVERSITY, Indonesia)
Risk is a situation that is uncertain and there is an element of danger, the consequences that could occur due to a process that is ongoing or upcoming events. One of them in construction, where activity in this activity, there is some risk that may occur and give a great impact in the success of the completion of the work. Approaches were made to the risks involved with understanding/identification of risk, risk measurement, risk mapping, the response to risk. So with the existence of such activities can provide a recommendation as to whether the risks are acceptable, divided, reduced or avoided. This research was conducted with descriptive quantitative research methods. The results of this study concluded that there were 7 risk factors in very high level understanding of contract documents i.e., different site condition, productivity, quality equipment/material quality, smooth cash flow, the competence of sub contractors, and the influence of the weather. Against the risk of handling very high i.e. by way of doing business – business everything possible so that it can reduce the level of risk that exists so that the work can be resolved properly and the third project targets can be achieved.